A Few Honest Words : The Kentucky Roots of Popular Music - Howard, Jason, 1981- (Book collections on Project MUSE., 2012)
In industry circles, musicians from Kentucky are known to possess an enviable pedigree -- a lineage as prized as the bloodline of any bluegrass-raised Thoroughbred. With native sons and daughters like Naomi and Wynonna Judd, Loretta Lynn, the Everly Brothers, Joan Osborne, and Merle Travis, it's no wonder that the state is most often associated with folk, country, and bluegrass music. But Kentucky's contribution to American music is much broader: It's the rich and resonant cello of Ben Sollee, the velvet crooning of jazz great Helen Humes, and the famed vibraphone of Lionel Hampton. I.